2013
DOI: 10.1111/cmi.12246
|View full text |Cite
|
Sign up to set email alerts
|

TheFrancisellaO-antigen mediates survival in the macrophage cytosol via autophagy avoidance

Abstract: Summary Autophagy is a key innate immune response to intracellular parasites that promotes their delivery to degradative lysosomes following detection in the cytosol or within damaged vacuoles. Like Listeria and Shigella, which use specific mechanisms to avoid autophagic detection and capture, the bacterial pathogen Francisella tularensis proliferates within the cytosol of macrophages without demonstrable control by autophagy. To examine how Francisella evades autophagy, we screened a library of F. tularensis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
62
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 38 publications
5
62
1
Order By: Relevance
“…In chemically fixed samples, bacteria, both phagosomal and cytosolic, were surrounded with electron-translucent areas, so-called halos (see Fig. S4A and B in the supplemental material), which were previously suggested to represent a bacterial capsule (17,22). However, in cryofixed samples, we could observe an electron-pale area only around cytosolic bacteria (Fig.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…In chemically fixed samples, bacteria, both phagosomal and cytosolic, were surrounded with electron-translucent areas, so-called halos (see Fig. S4A and B in the supplemental material), which were previously suggested to represent a bacterial capsule (17,22). However, in cryofixed samples, we could observe an electron-pale area only around cytosolic bacteria (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…noatunensis confirm that Francisella bacteria are indeed extremely polymorphic and indicate that the electron-translucent area around bacteria in chemically fixed samples is a fixation artifact. For chemically fixed F. tularensis in macrophages, a similar zone has been suggested to represent a capsule made of the polysaccharide O antigen (22). Nevertheless, in HPF samples, cytosolic bacteria were surrounded with an electron-pale area, which appeared to contain weakly contrasted material.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Avoiding autophagy is proposed as one of the immune evasion mechanisms adopted by F. tularensis (68). Studies conducted with M. tuberculosis have shown that ROS is required for autophagy-mediated elimination of intracellular BCG.…”
Section: Discussionmentioning
confidence: 99%
“…Since our results revealed an involvement of the O side chain in bacterial survival upon macrophage phagocytosis, we next investigated whether the O antigen affects intracellular trafficking to avoid bactericidal mechanisms, as found before for other bacterial pathogens (32)(33)(34). To this end, bacterial colocalization with the acidotropic dye LysoTracker was investigated at different time points postinfection.…”
Section: Resultsmentioning
confidence: 79%